Best Approximations and Kolmogorov and Trigonometric Widths of the Classes $B_{p,θ}^{Ω}$ of Periodic Functions of Many Variables - Stasyuk, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We obtain estimates exact in order for the best approximations and Kolmogorov and trigonometric widths of the classes $B_{p,θ}^{Ω}$ of periodic functions of many variables in the space $L^q$ for certain values of the parameters $p$ and $q$.